(untitled) (Bangladesh Journal of Pharmacology, 2015)
The aim of the current study was to evaluate the anticancer and apoptotic effects of alantolactone pyrazoline analogue in human non-small cell lung cancer (NCI-H460) cells. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetra-zolium bromide) assay was used to evaluate the cell viability while as fluorescence microscopy was used to assess the effect on apoptosis, cellular and nuclear morphology. Flow cytometry evaluated the effect of APA on cell cycle arrest in these cells. The results revealed that APA induced potent, time and dose-dependent cytotoxic effects on the growth of NCI-H460 cells. It also inhibited colony forming tendency as well as cell invasion capability of these cancer cells. APA induced dose-dependent nuclear and cellular morphological effects including chromatin condensation and DNA fragmentation. Flow cytometry revealed that the anticancer effects of APA might be due to its cell cycle arrest inducing tendency in G0/G1 phase of the cell cycle.